Role of generative artificial intelligence in the transformation of commercial activities in biopharmaceutical industry in Singapore - Li, Lei Lei (2024)
Generative artificial intelligence (AI) has emerged as a prominent topic of discussion, fueled by the proliferation of innovative platforms such as ChatGPT and Dali, which have captured the imagination of both individuals and businesses alike. With industry forecasts predicting significant revenue growth attributed to generative AI applications across various sectors, executives in the C-suite are increasingly recognizing its potential to unlock new opportunities in business.